What Are The Causes And Impacts Of Oil Price Volatility In The World Economy - Mohammed Saeed, Jemal (2005)
This paper looks at various aspects of oil price volatility and points out the most important factors and the impacts and attempts to find out where we are headed. The stability of the oil prices is the backone that the global economy needs to take future positive strides.